Pre-service EFL teachers’ competencies for teaching young learners - Hilal Alten; Müge Karakaş (Literacy Trek)
This explanatory study aims to identify certain competencies that teachers need to possess for teaching young and very young learners from the perspective of Turkish pre-service EFL teachers who are conducting their practicum studies within the last year of the teacher training program. In this mixed-method research, a Likert-type 5-point scale, which was developed using the Delphi technique, including 29 terms measuring different competencies and related interview questions, was used to collect data. Turkish pre-service EFL teachers’ points of view have been evaluated according to the factors and variables in the scale to reveal whether they feel competent enough to teach English to young learners during their teaching practicum and to what extent they implement their theoretical knowledge into classes. Interview questions were addressed to the two of the participants regarding their choices and results of the quantitative data analysis in the next phase of the study. The results at the end of this explanatory research pointed out that some pre-service teachers may get challenged more while teaching young learners for certain reasons.